Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376856
|View full text |Cite
|
Sign up to set email alerts
|

Household Surface Interactions: Understanding User Input Preferences and Perceived Home Experiences

Abstract: Households contain a variety of surfaces that are used in a number of activity contexts. As ambient technology becomes commonplace in our homes, it is only a matter of time before these surfaces become linked to computer systems for Household Surface Interaction (HSI). However, little is known about the user experience attached to HSI, and the potential acceptance of HSI within modern homes. To address this problem, we ran a mixed methods user study with 39 participants to examine HSI using nine household surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The findings of this research are consistent with previous study by Tigwell and Crabb [25] and Wilson et al [26], where found that peoples preferred smart technologies, such as colour-changing lighting and interactive artwork of their homes and that residents preferred smart home technologies that customized to their individual preferences of their living spaces.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this research are consistent with previous study by Tigwell and Crabb [25] and Wilson et al [26], where found that peoples preferred smart technologies, such as colour-changing lighting and interactive artwork of their homes and that residents preferred smart home technologies that customized to their individual preferences of their living spaces.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies that have found that residents prioritise visual aesthetics and ambience in their living spaces when incorporating smart technologies. For example, a study by Tigwell and Crabb [28] found that residents preferred smart technologies that enhanced the visual appeal of their homes, such as colourchanging lighting and interactive artwork. Another study by Wilson et al [29] found that residents valued smart home technologies that could be customised to their individual preferences and enhanced their living spaces' overall aesthetic.…”
Section: Figure 11 Preferred Interactive Intelligent Technologies For...mentioning
confidence: 99%
“…Insights into trust in automated demand-side management [21], novel interaction forms [68], end-user programming for smart home configuration [52], long-term user experience of automated ambient technology [23], and privacy aspects [75] Active and assisted living Many solutions for social robots and assistive functions have been introduced and investigated, but roll out on a large scale is pending Long-term acceptance aspects [13], individual differences in trust [61], human-robot interaction [37], and contextual design of digital assistants [2] approaches should feed into further instances of the above introduced preliminary design space that could help shape everyday automation experience into something desirable for the future.…”
Section: Manufacturingmentioning
confidence: 99%